Determinants of Infant Mortality in Bangladesh: A Nationally Surveyed Data Analysis - Rahman, Azizur; Rahman, Md. Sazedur; Rahman, Md. Ashfikur (International Journal of Child Health and Nutrition, 2019)
Background: It is well established that improving human health has direct obvious payoff on enhancing life expectancy along with economic growth. Infant mortality deliberately used to understand a countries overall public health status particularly child bearing mothers. But the prevalence of child mortality continues to be a prime public health concerns in Bangladesh. This study aims to investigate the impact of some geospatial, socioeconomic, demographic and health factors on infant mortality in Bangladesh. Methods: The study modeled infant mortality (aged 0-11 months) as the categorical dependent variable using 11 selected covariates from the 2014 Bangladesh Demographic and Health Survey (BDHS-2014) dataset. The Pearson-Chi square test and Binary Logistic Regression methods were utilized for the bivariate and multivariate analyses. Results: All the selected covariates were significantly associated with infant mortality in bivariate analysis. The results of the logistic regression revealed that illiterate father, household without toilet facility or having hanging toilet, multiple birth and small size at birth appeared at the significant risk factors for infant mortality. In contrast, receiving vitamin A dose and visiting in antenatal care revealed as protective factor for infant deaths. Conclusion: This study is uniquely addressed some several determinants which are the immediate cause of infant deaths. This evidence based empirical study suggests that more attention needs regarding to eliminate all kinds of child mortality in Bangladesh along with infant mortality.